Thermal economy analysis on deep peak regulation operation of supercritical 630 MW coal-fired unit - Zhang, Hongquan; Pang, Yongchao; Cui, Haocheng; Li, Jianchao; Wang, Weishu; Zhang, Zhen; Tang, Zibo; Hao, Liyu (Frontiers in Energy Research, 2025)
With the development of new energy and the proposal of the “double carbon” target, accelerating the flexibility transformation of coal-fired generating units and guiding coal-fired generating units to participate in deep peak shaving have become an effective means of absorbing new energy to ensure the stability of the grid. In this paper, the operation performance of a supercritical 630 MW coal-fired unit with 16.67%–100% rated load is obtained through experiments. The results show that: when the unit load is greater than 50% rated load, the economy is higher; when the unit load continues to decline from 50% rated load, the unit heat rate, absolute electrical efficiency, standard coal consumption and other economic indicators drop rapidly, and the operation economy becomes worse. When the load of the unit is reduced to 105 MW, which is 16.67% of the rated load, the absolute electrical efficiency is reduced to 38.54%, the heat of the unit is increased to 9,340 kJ/(kW·h), and the standard coal consumption of the power generation is increased to 359.25 g/(kW·h). The test results of the unit can provide a reference for the flexibility adjustment and operation optimization of the same type of units.